2019
DOI: 10.29008/etc2019-293
|View full text |Cite
|
Sign up to set email alerts
|

External heat transfer on nozzle guide vanes under highly swirled combustor outlet flow

Abstract: Nozzle Guide Vanes aero-thermal performance is commonly assessed in the industry using tangentially-averaged quantities, imposed at the combustor-turbine interface as inlet conditions for RANS models. However, recent studies have shown that scale-resolving approaches can reproduce the impact of unsteady fluctuations on turbulent mixing. An experimental test case with a combustor simulator and a nozzle cascade is investigated, comparing two numerical modelling strategies: i) Scale-adaptive simulation (SAS) incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…However, this behavior is not observed for different span values: in fact, at 25 and 75% of the span, it can be noted that the RANS generally tends to assume values of adiabatic effectiveness that are higher than those of SBES, especially on the SS. This demonstrates that, as expected and already demonstrated in the literature [34,35], it is essential to include the effects of unsteadiness on turbulent mixing, which otherwise would be strongly under-predicted.…”
Section: Evaluation Of the Airfoil Loads And Adiabatic Effectivenesssupporting
confidence: 71%
See 1 more Smart Citation
“…However, this behavior is not observed for different span values: in fact, at 25 and 75% of the span, it can be noted that the RANS generally tends to assume values of adiabatic effectiveness that are higher than those of SBES, especially on the SS. This demonstrates that, as expected and already demonstrated in the literature [34,35], it is essential to include the effects of unsteadiness on turbulent mixing, which otherwise would be strongly under-predicted.…”
Section: Evaluation Of the Airfoil Loads And Adiabatic Effectivenesssupporting
confidence: 71%
“…The authors pointed out that SAS predicts better than RANS the recirculating region inside the combustor, which has a large impact over the resulting gas temperature at the turbine inlet and over the coolant and the main stream mixing process, even if it mildly affects the velocity field. As a matter of fact, even if RANS is sufficient to predict the aerodynamics of the turbine and to provide a reasonably accurate solution with a low computational effort [33], Scale-Resolving methods are required to assess satisfactorily the thermal behavior of the vanes, as demonstrated by subsequent works [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it can be stated that CFD is satisfactorily replicating the coolant alternate spread on the higher/lower half of the PS/SS due to the main flow swirling structure, although there is yet wide margin for improvement. In fact, based on available data in the open literature, it is expected that more advanced CFD modelling techniques (such as scale-resolving methods) can help in overcoming the limitations of RANS in accurately reproducing the mixing between coolant and main streams [23] [32].…”
Section: Film-cooling Adiabatic Effectivenessmentioning
confidence: 99%
“…As a matter of fact, several studies have shown that the vortical structures that characterize the combustor flow field are able to maintain a non-negligible part of its characteristics even at a relevant distance from the regions of the combustor where they are generated, in correspondence to the swirler. In particular, at the exit of the combustor, a highly non-uniform velocity distribution can be observed, characterized by high swirl and pitch components, along with temperature non-uniformities ("hot streaks") [1] and high turbulence levels [2][3][4] that can be conserved up to the inlet of the following component, the first-stage nozzle of the high-pressure turbine (HPT), as proven both experimentally and numerically [5][6][7][8]. Such severe conditions are particularly exacerbated due to the employment of modern gas turbine (GT) combustors, such as lean-burning systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the context of the project FACTOR (full aerothermal combustor-turbine interactions research), SAS simulations have been performed in order to study the aerothermal field on the vanes that were equipped on a non-reacting test rig of a lean-burn annular combustor. As a matter of fact, benchmarking the CFD predictions to the available experimental results obtained by Bacci et al [20,35], Andreini et al [2] demonstrated that SAS simulations describe the recirculating area inside the combustor better than RANS, thus improving the prediction of the turbulent mixing between the hot main flow coming from the combustor and the cooling flows [3]. An alternative to SAS and DES is represented by the stressblended eddy simulation (SBES) model, that has become increasingly popular in recent years since it allows modeling of the boundary layers regions using RANS instead of using the more expensive LES, in terms of computational resources required [36].…”
Section: Introductionmentioning
confidence: 99%